2018
DOI: 10.1002/lsm.22933
|View full text |Cite
|
Sign up to set email alerts
|

5‐ALA in the management of malignant glioma

Abstract: Background: Patients suffering from malignant gliomas have a poor prognosis. For the surgical treatment of these tumors, 5-aminolevulinic acid (5-ALA) has become a new standard. Aims: This review intends to provide an overview over current status, significance, limitations, and future perspectives of 5-ALA based fluorescence guided surgery and photodynamic therapy for brain tumor patients. Materials and Methods: From peer reviewed publications on the many aspects connected with this topic, those with potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(167 citation statements)
references
References 236 publications
(252 reference statements)
3
160
0
4
Order By: Relevance
“…Increases in peripheral ALA have been shown to increase brain levels of PPIX 2.5‐fold in the mouse cortex (Demyanenko, Uzdensky, Sharifulina, Lapteva, & Polyakova, ). Clinically, oral administration of ALA is used to delineate gliomas via the fluorescent properties of PPIX, which gliomas accumulate in greater amounts than non‐malignant brain tissue (Stepp & Stummer, ), providing evidence that in humans increases in ALA lead to elevations of PPIX. Finally, pre‐treatment with 200 mg/kg ALA, which is converted to PPIX, decreased [ 11 C]PBR28 uptake in TSPO‐rich regions, such as the heart and lungs, by 57%–80%, respectively, in rats in vivo using PET (Ozaki et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in peripheral ALA have been shown to increase brain levels of PPIX 2.5‐fold in the mouse cortex (Demyanenko, Uzdensky, Sharifulina, Lapteva, & Polyakova, ). Clinically, oral administration of ALA is used to delineate gliomas via the fluorescent properties of PPIX, which gliomas accumulate in greater amounts than non‐malignant brain tissue (Stepp & Stummer, ), providing evidence that in humans increases in ALA lead to elevations of PPIX. Finally, pre‐treatment with 200 mg/kg ALA, which is converted to PPIX, decreased [ 11 C]PBR28 uptake in TSPO‐rich regions, such as the heart and lungs, by 57%–80%, respectively, in rats in vivo using PET (Ozaki et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concept entails some practical advantages. A combination of NIR illumination with fibre-based detection reduces the system's susceptibility to room light interference, which is normally in the visible light spectrum [31], implying that surgical procedures could be performed under normal lighting conditions [11]. Longer wavelengths would further decrease interference of ambient light as well as increase the imaging depth [19,29], but at the expense of a reduced spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from system configuration, the employed contrast mechanism also affects the feasibility of adopting an imaging method for intraoperative use. Fluorescence guided surgery, as one of the most commonly exploited techniques, has provided useful information on the cellular and molecular scale for brain tumour resection [2,[9][10][11]. However, the use of fluorescent dyes in the human brain is limited by many factors, such as tumour selectivity, fluorophore uptake due to the blood-brain-barrier, fluorophore brightness and toxicity, photobleaching, injection timings, dose constraints [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several Phase I/II clinical trials have demonstrated improvement in overall survival times and progression‐free survival . As recently reviewed by Stepp and Stummer , the combination in the use of ALA‐PpIX for fluorescence image‐guided tumor resection followed by intracavitary photodynamic therapy is particularly compelling. Interstitial PDT, exploiting the tumor selectivity of ALA‐PpIX, has also been investigated for destruction of metastatic tumors in the brain and has shown significant efficacy .…”
Section: Clinical Application Examplesmentioning
confidence: 99%